Clinico-aetiological Profile of Congenital Hypothyroidism - Karki, Subhana Thapa; Rai, Ganesh Kumar; Karki, Buddha Bdr; Gurung, Roshma (Journal of Nepal Paediatric Society, 2016)
Introduction: Thyroid hormone is critical for normal brain development in the early postnatal months. Biochemical diagnosis must be made soon after birth and effective treatment must be initiated promptly to prevent irreversible brain damage. Early diagnosis and adequate treatment from the first weeks of life result in normal linear growth and development. This study was conducted to find out the clinical features suggestive of congenital hypothyroidism and also its causation. Materials and Methods: This was a hospital based retrospective study of 40 congenital hypothyroid children conducted at endocrine unit of Kanti Children’s hospital from 2067 to 2072. All congenital hypothyroid children were reviewed in detail and frequency of signs/symptoms was calculated and also the possible causes were established using ultrasonography and scintigraphy.Results: Out of 40 congenital hypothyroid children 55% were male and 45% were female with M: F ratio of 1.23:1.Common age of presentation of congenital hypothyroidism was 6 to 12 months. The most frequent symptoms were decreased activity/ lethargy (78.9%) followed by stunted height (68.4%) and hypotonia (65.8%).Technetium thyroid scan was performed in 19 cases among which thyroid agenesis was the most common cause of congenital hypothyroidism (42.1%) followed by dyshormonogenesis (31.6%) and ectopic thyroid (26.3%).Conclusion: Early diagnosis of congenital hypothyroidism is possible in some children based on clinical features followed by biomedical investigation soon after birth.J Nepal Paediatr Soc 2016; 36(2):126-130